Investigation the Performance of an Evacuated Tube Solar Collector Filled with MWCNT/ Water Nanofluid Under the Climate Conditions of Al-Hilla (Iraq) - Khudair, Nagham Yass; Husain, Ahmed Kadhim (Journal of Petroleum Research and Studies, 2024)
The main obstacles to securing the future of humanity are the rising energy demand and the constrained supply of conventional energy sources. In order to guarantee the sustainability of energy in this world for the present and the future, solar energy is a desirable source of energy. Solar thermal collectors with evacuated tubes are primarily employed in domestic settings. Even in low-temperature applications, replacing the working fluid with nanofluid can improve heat transfer. The effect of Multi-Walled Carbon Nanotubes (MWCNT) and water nanofluid as working fluids in evacuated tube solar collectors(ETSC) is used to investigate the collector's thermal performance experimentally. Three different volume fraction of (MWCNT) nanoparticles of (0.01%, 0.03% and 0.05%) were examined at various volume flow rates ranging from (1 to 3 L/min). Experiments were performed in Al –Hilla, Iraq. The results show an enhancement in the efficiency with increase in the volume fraction of(MWCNT)nanoparticles and volume flow rate (i.e. concentration (0.05%) and volume flow rate (3L/min). The temperature difference of the fluid at concentration (0.05%) and volume flow rate (1L/min) increased up to (86.84 %) with adding (MWCNT) nanoparticles compared with the water. The results showed, maximum efficiency enhancement of the collector at concentration (0.05%) and volume flow rate (3L/min) about (69.63%) compared with water.